Conversion Rate from Laparoscopic to open Cholecystectomy in AL-kindy Teaching Hospital, Baghdad - Rashid, Firas M (AL-Kindy College Medical Journal, 2020)
Background: laparoscopic cholecystectomy (LC) is getting popularity for the treating of symptomatic gall bladder disease; conversion from laparoscopic to open cholecystectomy (OC) is also common.Objective : To find out the prevalence of causes, risk factors of conversion from LC to OC among  patient suffering from gall bladder disease, and  to explore the most common causes of conversion from laparoscopic to open cholecystectomy.Methods: This prospective study was conducted in the department of general surgery at Alkindy teaching hospital from first of January 2016 to the end of December 2017 .Nine hundred twenty patient were included. Patient age, gender, history of previous abdominal scar, common bile duct stone, ERCP, duration of symptom was included in our study.Results: Seven hundreds twenty –seven patients 74.48% were females and 191  26.52% were males. The mean age of patient presented with gall bladder disease was 40.43 years. Thirty –eight patients were converted to open cholecystectomy. The most common cause of conversation was dense adhesions 42.1% - followed by bleeding 30.1%. Other common causes of conversion were biliary anomalous anatomy 10.5%, common bile injury 5%, visceral injury and technical failure  7%.Conclusion: The main perioperative cause for OC was dense adhesion around gall bladder and the male gender, increasing age, history of common bile duct stone removed by previous ERCP, history of previous surgery, are independent risk factors of difficult laparoscopic cholecystectomy.